Decision Analysis Modelling of Costs and Outcomes following Cefepime Monotherapy in Canada - Michael T Halpern; Ruth E Brown; Martine Drolet; Sonja V Sorensen; Lionel A Mandell (Canadian Journal of Infectious Diseases)
OBJECTIVE: To evaluate the comparative cost of treatment and intermediate outcomes (percentage resistant organisms, days in hospital, etc) among cefepime and alternative parenteral antibiotics used for empiric monotherapy.